Prevalence of congenital malformations diagnosed in the first 24 hours of life (Colombia Medica, 1989)
Congenital malformations are not at all uncommon problems in Cali, Colombia. A survey of 9,300 newborns from the Hospital Universitario del Valle revealed 2.34% of congenital malformations detected at the first clinical examination made during the first 24 hours of staying at the hospital.